Epigenetic regulation in premature ovarian failure: A literature review - Wang, Jing; Sun, Xiguang; Yang, Zongxing; Li, Sijie; Wang, Yufeng; Ren, Ruoxue; Liu, Ziyue; Yu, Dehai (Frontiers in Physiology, 2023)
Premature ovarian failure (POF), or premature ovarian insufficiency (POI), is a multifactorial and heterogeneous disease characterized by amenorrhea, decreased estrogen levels and increased female gonadotropin levels. The incidence of POF is increasing annually, and POF has become one of the main causes of infertility in women of childbearing age. The etiology and pathogenesis of POF are complex and have not yet been clearly elucidated. In addition to genetic factors, an increasing number of studies have revealed that epigenetic changes play an important role in the occurrence and development of POF. However, we found that very few papers have summarized epigenetic variations in POF, and a systematic analysis of this topic is therefore necessary. In this article, by reviewing and analyzing the most relevant literature in this research field, we expound on the relationship between DNA methylation, histone modification and noncoding RNA expression and the development of POF. We also analyzed how environmental factors affect POF through epigenetic modulation. Additionally, we discuss potential epigenetic biomarkers and epigenetic treatment targets for POF. We anticipate that our paper may provide new therapeutic clues for improving ovarian function and maintaining fertility in POF patients.